Communicating Sustainability: A Postoccupancy Evaluation of the David Brower Center. (October 2014) - Cranz, Galen; Lindsay, Georgia; Morhayim, Lusi; Lin, Annie
As the United States adjusts to the necessity of ecological sustainability, buildings play an important role because of their use of resources—and because they are potent nonverbal symbols of new societal values. The David Brower Center in Berkeley, California, strives to be a model for sustainability. Environmental impact is often the focus of those concerned with sustainability, but here, additionally, the designers aim to raise public awareness of sustainability through the building. For this reason, this building became the site for a postoccupancy evaluation class exercise; architecture students analyzed the building and what it communicates about sustainability from the perspective of its users. Findings indicate that many people did not adequately read the building's green design characteristics: Social and symbolic communication could be improved by increasing signage and evolving clearer symbolism for "green."